Early international entrepreneurship in China: Extent and determinants - Wim Naudé; Stephanié Rossouw (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
We use data on 3,948 Chinese firms obtained from the World Bank's Investment Climate Private Enterprise Survey to investigate early international entrepreneurship (international new ventures) in China. The extent of early international entrepreneurship in China is significant: 65 per cent of the exporting firms start export operations within three years. Foreign shareholders within the firm and an entrepreneur with previous exporting experience are noted to significantly increase the probability that a firm internationalizes early. However, we find marked differences in the behaviour of indigenous and foreign-invested firms. Thus, while business networks are significant for firms wishing to export indirectly and for older indigenous firms, it is noted to delay the internationalization process of indigenous firms. Also, for an indigenous firm, the greater the foreign experience of its entrepreneur, the less likely it is to start exporting early.
Keywords: L26; L25; F14; F23; O53; 330; entrepreneurship; internationalization; international new ventures; exports; China; Multinationales Unternehmen; China